Kebijakan Pemerintah dalam Upaya Perlindungan Pengungsi Asing - Zainuddin Zainuddin; Ismail Koto (Jurnal Penelitian Hukum De Jure, 2025)
As part of its responsibility to address refugee-related issues, Indonesia enacted Presidential Regulation No. 125 of 2016 concerning the Handling of Refugees from Abroad. This study is more in-depth than previous studies because it focuses on more specific legal regulations at the presidential regulation level. This provides the legal basis for the protection of foreign refugees in Indonesia and serves as the official guideline for managing asylum seekers and international refugees. This regulation is more operational, for example, shelter mechanisms such as shelter, accommodation and health and education, as well as basic services, and coordination with UNHCR/IOM, but does not provide formal legal status for refugees. One implementation is the relocation of asylum seekers from Immigration Detention Centers (Rudenim) to temporary shelters, thus enabling the provision of basic needs, which is facilitated and funded by the International Organization for Migration (IOM). The main differences between the international obligations of ratifying conventions and domestic authority through Presidential Regulations lie in their source, binding nature, and implications for the legal status and rights of refugees specifically. This regulation is seen as an alternative to ratifying the 1951 Convention and the 1967 Protocol Relating to the Status of Refugees, which Indonesia has not yet ratified. Presidential Regulation Number 125 of 2016 outlines several important provisions, including key definitions, detention mechanisms, shelter procedures, and protection measures for asylum seekers and refugees. This regulation consists of 45 articles detailing the coordination mechanism between government agencies in managing refugees. Based on Article 2 paragraph (1), the handling of asylum seekers and refugees is carried out through cooperation between the central government and the United Nations (UN).